RTI with differentiated instruction, grades 6-8 a classroom teacher's guide - O'Meara, Jodi.; Sage eBooks (Thousand Oaks, Calif. : Corwin ; London : SAGE, 2011)
Written in a practical format with lesson plans and examples this book gives middle school teachers a streamlined strategy for merging differentiated instruction and RTI.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Remedial teaching -- United States; Slow learning children -- Education -- United States; Learning disabled children -- Education -- United States; Response to intervention (Learning disabled children); Individualized instruction; Electronic books